Mimicking the effects of spaceflight on bone: Combined effects of disuse and chronic low-dose rate radiation exposure on bone mass in mice. (November 2017) - Yu, Kanglun; Doherty, Alison H.; Genik, Paula C.; Gookin, Sara E.; Roteliuk, Danielle M.; Wojda, Samantha J.; Jiang, Zhi-Sheng; McGee-Lawrence, Meghan E.; Weil, Michael M.; Donahue, Seth W.
Abstract: During spaceflight, crewmembers are subjected to biomechanical and biological challenges including microgravity and radiation. In the skeleton, spaceflight leads to bone loss, increasing the risk of fracture. Studies utilizing hindlimb suspension (HLS) as a ground-based model of spaceflight often neglect the concomitant effects of radiation exposure, and even when radiation is accounted for, it is often delivered at a high-dose rate over a very short period of time, which does not faithfully mimic spaceflight conditions. This study was designed to investigate the skeletal effects of low-dose rate gamma irradiation (8.5 cGy gamma radiation per day for 20 days, amounting to a total dose of 1.7 Gy) when administered simultaneously to disuse from HLS. The goal was to determine whether continuous, low-dose rate radiation administered during disuse would exacerbate bone loss in a murine HLS model. Four groups of 16 week old female C57BL/6 mice were studied: weight bearing + no radiation (WB+NR), HLS + NR, WB + radiation exposure (WB+RAD), and HLS+RAD. Surprisingly, although HLS led to cortical and trabecular bone loss, concurrent radiation exposure did not exacerbate these effects. Our results raise the possibility that mechanical unloading has larger effects on the bone loss that occurs during spaceflight than low-dose rate radiation.